Chromosome-Level Genome Assembly of the Green Peafowl (Pavo muticus). (2nd February 2022) - Zhang, Xinyuan; Lin, Chuyu; Li, Haimeng; Liu, Sixia; Wang, Qing; Yang, Shangchen; Shi, Minhui; Sahu, Sunil Kumar; Zhu, Yixin; Wang, Jiangang; Huang, Junxuan; Hu, Yiyin; et al.
Abstract: The green peafowl ( Pavo muticus ) is facing a high risk of extinction due to the long-term and widespread threats of poaching and habitat conversion. Here, we present a high-quality chromosome-level genome assembly of the green peafowl with high contiguity and accuracy assembled by PacBio sequencing, DNBSEQ short-read sequencing, and Hi-C sequencing technologies. The final genome size was estimated to be 1.049 Gb, whereas 1.042 Gb of the genome was assigned to 27 pseudochromosomes. The scaffold N50 length was 75.5 Mb with a complete BUSCO score of 97.6%. We identified W and Z chromosomes and validated them by resequencing 14 additional individuals. Totally, 167.04 Mb repetitive elements were identified in the genome, accounting for 15.92% of the total genome size. We predicted 14, 935 protein-coding genes, among which 14, 931 genes were functionally annotated. This is the most comprehensive and complete de novo assembly of the Pavo genus, and it will serve as a valuable resource for future green peafowl ecology, evolution, and conservation studies.